Potensi Agrowisata Sebagai Upaya Tindakan Konservasi Guna Mewujudkan Pembangunan Berkelanjutan : (Studi Kasus Di Kampung Cinyurup Keluruhan Juhut Kecamatan Karangtanjung Kabupaten Pandeglang Provinsi Banten) - Nuniek Hermita (Faculty of Agriculture, Pattimura University, 2015)
Cinyurup kampung has the potential of high biodiversity of flora and fauna, which often have problems of environmental degradation. The purpose of the research was to identify agritourism potential as effort for identifying agritourism potential as conservative action to realize sustainable development in the region. It used descriptive squalitative method with data collection through observation, interview, questionnaire distribution and documentary study. The result indicted that there is agritourism potential such as physical condition; agricultural commodity, sheep farming; and other tourism supporting potential. Visitors can enjoy directly natural panorama that is cool, clean and beautiful and do recreation tourism attraction activity and scientific activity such as cultivation and talas beneng commodity processing to be main product, making compost fertilizer, biogas and field laboratory. Agritourism activity in Cinyurup kampung, kelurahan Juhut Karangtanjung district, Pandeglang regency Banten is proper step in conservation action. Because conservation areas such as management, usage and conservation on biodiversity having potential as agritourism can give economic profit for society and ecosystem balance in Gunung Karang area. So, it may be consideration for future interest and realize sustainable development.